2019
DOI: 10.1002/acm2.12700
|View full text |Cite
|
Sign up to set email alerts
|

Surface guided radiotherapy (SGRT) improves breast cancer patient setup accuracy

Abstract: Purpose The purpose of the study was to investigate if surface guided radiotherapy (SGRT) can decrease setup deviations for tangential and locoregional breast cancer patients compared to conventional laser‐based setup (LBS). Materials and Methods Both tangential (63 patients) and locoregional (76 patients) breast cancer patients were enrolled in this study. For LBS, the patients were positioned by aligning skin markers to the room lasers. For the surface based setup (SBS), an optical surface scanning system wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
97
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(106 citation statements)
references
References 16 publications
7
97
0
2
Order By: Relevance
“…There is a broad agreement on the supremacy of SGRT over 3-point laser-based patient setup, when the surface serves as a surrogate for the target positioning, i.e. breast and other skin-near targets [13,16,[21][22][23][24][25][26][27][28][29][30]. For deeper situated targets, surface imaging should be used with caution [13,22,31,32].…”
Section: Clinical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a broad agreement on the supremacy of SGRT over 3-point laser-based patient setup, when the surface serves as a surrogate for the target positioning, i.e. breast and other skin-near targets [13,16,[21][22][23][24][25][26][27][28][29][30]. For deeper situated targets, surface imaging should be used with caution [13,22,31,32].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…In this context, it has been shown that surface-guided correction of the arm posture also improved the breast position [13,16,27,30]. Nevertheless, some factors can affect the accuracy in surface-guided patient setup, such as patient motion [35], surface shadowing [16], selection of the region-of interest (ROI) [14], absence of anatomical gradients in the patient (e.g. very flat surfaces) and anatomical changes throughout the treatment [21,28,36].…”
Section: Breast Positioningmentioning
confidence: 99%
“…Currently, no guidelines exist in terms of rotational tolerances for SGRT and no recommendations are provided by the vendors. Default settings are in the range 3–5° and a value of 3° is probably more common and used in a recent study by Kügele et al . Based on our findings, clinically we now strictly enforce a 2° rotational tolerance before we start treatment to minimize vertical setup errors as a result of the rotations.…”
Section: Discussionmentioning
confidence: 87%
“…9 The advantage of using surface scanning is that the information from the surface can improve the patient setup compared to in-room lasers. [10][11][12] Also, a surface scan takes seconds, in comparison to minutes for MVCT. Thus, surface scanning has the potential to increase the accuracy, without substantially adding time for setup compared to setup with in-room lasers.…”
Section: Introductionmentioning
confidence: 99%